The threats on the biodiversity of Bisotun Wildlife Refuge and Bisotun Protected Area (BPA & BWR) in the west region of Iran - MAHDI REYAHI-KHORAM; MRZIEH RIZVANDY; REIHANEH REYAHI-KHORAM (Society for Indonesian Biodiversity, 2014)
Reyahi-Khoram M, Rizvandy M, Reyahi-Khoram R. 2014. The threats on the biodiversity of Bisotun Wildlife Refuge and Bisotun Protected Area (BPA & BWR) in the west region of Iran. Biodiversitas 15: 67-74. Nature is necessary for the preservation of species and biodiversity richness; as a result, it has been protected for thousands of years. Bisotun Protected Area and Bisotun Wildlife Refuge (BPA & BWR) with about 95000 hectares is located in Kermanshah province in the west of Iran. The object of this study is to determine the physical properties and analyze the constraints that threaten the BPA & BWR. This research was conducted during the period from May, 2011 to November, 2012 in BPA & BWR. In this research, various animal and plant species were recognized through documentary analysis and also directs field observations. The obtained result indicates that major threats have occurred in biodiversity and ecosystem of BPA & BWR during 1980-2010. During these years, the study area has completely failed and lost some of its biological diversity. Limiting factors that affect wildlife population growth including destruction and conversion of habitats, unauthorized hunting and high frequency presence of animal and human, have influenced the restoration potential of wildlife, the habitats and other conservation areas.